PENYULUHAN IMUNISASI DASAR ANAK PADA MASA ADAPTASI KEBIASAAN BARU - Hesteria Friska Armynia Subratha (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2021)
The government has designated Coronavirus Disease 2019 (COVID-19) as a non-natural disaster in the form of an outbreak/pandemic, this determination is followed by efforts to prevent the spread of the corona virus through social restrictions, including restrictions on crowds, travel restrictions, implementation of isolation, delays and cancellations. events, as well as the closure of facilities and public service arrangements. This condition also affects the schedule and procedures for immunization services both at posyandu, puskesmas and other health facilities, including private ones). Nationally, Regency/City Immunization Coverage which reaches 80% of complete basic immunization is 37.2% of the target of 79.3% or the percentage of performance achievement is 46.9%. Universal Child Immunization (UCI) Villages are villages where 80% of the total number of infants in the village have received complete basic immunization within one year. The coverage of UCI Villages/Urbans in Buleleng Regency, Bali Province in 2020 is 99.3%, a decrease from 2019 which reached 100%. Through this health education activity, it is expected to increase public knowledge about basic immunization for children during the adaptation period of new habits at the Posyandu, Kekeran Village, Busungbiu District, Buleleng Regency, Bali with various efforts in joint activities with all parties.